Preparation, Antibacterial Potential, and Antibacterial Components of Fermented Compound Chinese Medicine Feed Additives - Zou, Wanjie; Huang, Honglan; Wu, Huadong; Cao, Yuandong; Lu, Wei; He, Yuyong (Frontiers in Veterinary Science, 2022)
This experiment was conducted to compare the antibacterial ability and to identify the antibacterial components of different fermented compound Chinese medicine feed additives in order to develop one fermented compound Chinese medicine feed additive product that can effectively alleviate metritis, vaginitis and mastitis of sows. Oxford cup method and double dilution method were used to compare the antibacterial ability of three fermented compound Chinese medicine feed additives (A, B and C), UHPLC-QE-MS based untargeted metabolomics was used to identify the antibacterial components of fermented compound Chinese medicine feed additives. Results showed that among fermented compound Chinese medicine feed additives A, B and C, additive A had the strongest ability to inhibit the growth of Staphylococcus aureus, Salmonella cholerae suis, Escherichia coli and Streptococcus agalactiae. The MIC and MBC of additive A were the lowest for Staphylococcus aureus compared to that for the other three pathogens. The concentrations of 23 Chinese medicine ingredients (ellagic acid, guanine, camphor, L-valine, sinapine, dipropylphthalate, 3-hydroxy-5-isopropylidene-3,8-dimethyl-2,3,3a,4,5,8a-hexahydro-6(1H)-azulenone, 7-dihydroxy-2-(4-hydroxyphenyl)-8- [3,4,5-trihydroxy-6-(hydroxymethyl)oxan-2-yl]-6-(3,4,5-trihydroxyoxan-2-yl)chromen-4-one, acetylcholine, farrerol, pyrogallol, ethyl gallate, demethylwedelolactone, methylgallate, kaempferide, gallic acid, eriodictyol, threonic acid, inositol, 3',4',7-trihydroxyflavanone, taxifolin, asiatic acid and isorhamnetin) in additive A were significantly (P < 0.05 or P < 0.01) higher than that in additive B, respectively. It is concluded that the mixture composed of 23 active components in fermented compound Chinese medicine feed additive A plays important role in inhibiting the growth of Staphylococcus aureus, Salmonella cholerae suis, Escherichia coli and Streptococcus agalactiae.